TOKSISITAS AKUT DAUN Justicia gendarussa Burm - Elya, Berna; Amin, Juheini; Emiyanah, Emiyanah (Makara Journal of Science, 2010)
Acute Toxicity of Justicia gendarussa Burm. Leaves. Preminelary experiment showed that ethanolic extract of gandarusa leaves (Justicia gendarussa Burm.) could decreased uric acid blood level on rats. The aim of this experiment was to determine of the value LD50 and liver function based on activities of aminotransferase. Animals test which were used in this experiment were 50 males and 50 females white mice. They were divided into 5 groups. Group 1 as control group was given aquadest. Group 2-5 were treated by ethanolic extract of gandarusa leaves with dosage 4, 8, 16, and 32 g/kg bw. The LD50 value was determined by the amount of death in group during 24 hours after giving a single dose of test substance. The result showed that the highest dose was practically non toxic with LD50 value of 31.99 g/kg bw (male groups) and 27.85 g/kg bw (female groups). Measurement of aminotransferase activity was done by using colorimetric method. The result of ANOVA analysis for liver function showed that the giving test substance 4 g/kg bw –16 g/kg bw was not significantly different between treated groups and control group.